Caffeinated beverages contribute to a more efficient inflammatory response: Evidence from human and earthworm immune cells. (December 2019) - Alves, Audrei de Oliveira; Weis, Grazielle Castagna Cezimbra; Unfer, Taís Cristina; Assmann, Charles Elias; Barbisan, Fernanda; Azzolin, Verônica Farina; Chitolina, Bruna; Duarte, Thiago; Ribeiro-Filho, Euler Esteves; Duarte, Marta Maria Medeiros Frescura; Boligon, Aline; Vélez-Martin, Eduardo; et al.
Abstract: The role of caffeinated beverages on efficiency of acute inflammatory responses is not yet fully understood. This study analyzed the effect of five hot water extracts, coffee (CO), black/green tea (BT/GT), yerba mate (YM), and guarana (GU) on inflammatory modulation of non-activated human peripheral blood mononuclear cells (PBMCs), yeast-activated human neutrophils, and granulocytic coelomocytes from Eisenia fetida earthworm. Based on preliminary tests, a concentration of 10 μg/mL was chosen for subsequent assays, as at this concentration, the extracts exhibited antioxidant, genoprotective, and non-cytotoxic properties. Immunoassays using 24-h PBMC supernatant showed that all extracts decreased levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, and IFN-γ), and increased levels of the anti-inflammatory cytokine, IL-10. Further, these extracts induced overexpression of cytokine genes in 24-h cultures. These results suggest that an increase in the levels of mRNAs and/or inactive cytokines in the cytoplasm improves the "immune cytokine response. Analysis of the yeast encapsulation processes, and production of human neutrophils and coelomocyte extracellular DNA traps suggests that extracts also improve the immune response in humans and earthworms. However, for E. fetida, the intensity of these results varied from extract. Overall, our results suggest that caffeinated beverages may improve an organism's efficiency against acute inflammatory processes. Graphical abstract: Image 1 Highlights: Usual preparation of caffeinated beverages with hot water and short extraction time has immunomodulatory effect. Methylxanthines have beneficial effects on chronic inflammatory states associated with non-transmissible chronic diseases. Protocols using humans and earthworms immune cells suggest that caffeinated beverages possibly increase immune response. Cytokines genes upregulation produce an "immune reserve" improving body's efficiency against acute inflammatory processes.